Polycystins, calcium signaling and pathogenesis of polycystic kidney disease - del Senno, Laura (Henry Stewart Talks, 2007)
Clinical and genetic aspects of polycystic kidney disease, The polycystins (PC1, PC2), The PC2 channel, PC1 and PC2 subcellular location and interaction, Mechanosensory function of the ciliary PC1/PC2 complex, PC signaling and calcium homeostasis, PC1, calcium levels and cell proliferation, PC1, cAMP signaling and cell proliferation, PCs and physiopathologic calcium signaling